2010 2nd International Conference on Signal Processing Systems 2010
DOI: 10.1109/icsps.2010.5555386
|View full text |Cite
|
Sign up to set email alerts
|

Performance of multiuser MIMO system employing block diagonalization with antenna selection at mobile stations

Abstract: Abstract-This paper reports investigations into capacity of a multiuser Multiple-Input Multiple-Output (MIMO) system which uses a block diagonalization (BD) scheme with antenna selection at mobile stations (MSs). It is shown that the antenna selection at MSs improves capacity while at the same time it offers an effective solution to hardware size and cost. Also it is advantageous from the point of view of simplicity of signal processing at mobile stations. Two antenna selection schemes are investigated, one is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Because the purpose of the method in [32], [33] is basically the same as that of the AS method, the quantitative comparison in terms of the BER performance and calculation complexity should be evaluated as future work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the purpose of the method in [32], [33] is basically the same as that of the AS method, the quantitative comparison in terms of the BER performance and calculation complexity should be evaluated as future work.…”
Section: Resultsmentioning
confidence: 99%
“…Methods that reduce the number of pattern nulls for the IUI in the BD algorithm are already proposed in [32] and [33]. Because the former method reduces the number of pattern nulls by the antenna selection at the UT, the basic idea in [32] is the same as that in the AS method. However, the additional method in [34] is used as the measure on the antenna selection in [32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors have concluded that the application of antenna selection schemes improves channel capacity while reducing complexity and cost of the systems. M. Naeem and D.C. Lee [15] have presented an optimised joint user scheduling and receive antenna selection algorithm based on Binary Particle Swarm Optimization (BPSO) approach to improve the performance of MU-MIMO system.W. Ni and X. Dong have considered case of MIMO downlink scenario and presented hybrid block diagonalization scheme to improve the capacity performance of conventional BD scheme.…”
Section: Related Workmentioning
confidence: 99%